Preparation and Simulation of Polycarbonate Hollow-Fiber Membrane for Gas Separation - Reza Sohrabi, Mahmoud; Marjani, Azam; Moradi, Sadegh; Davallo, Mehran; Shirazian, Saeed (Asian Journal of Chemistry, 2010)
In present studies, the gas separation in hollow-fiber membranes was investigated theoretically and experimentally. Hollow fibers were prepared by melt-extrusion method at speed of 110 m/ min. Simulations were performed for gas absorption in liquid absorbents. Simulations were performed for absorption of CO2 in aqueous solution if K2CO3. Moreover, the simulation results were validated with experimental data obtained from literature for physical absorption of CO2. The simulation results were in good agreement with experimental data. Simulations showed percentage removal of 75 % for CO2 removal. The results indicated that hollow-fiber membranes have a good performance in the area of gas absorption.